An inhalable powder formulation based on micro-and nanoparticles containing 5-fluorouracil for the treatment of metastatic melanoma - Zatta, Kelly Cristine; Frank, Luiza A.; Reolon, Luciano Antonio; Amaral-Machado, Lucas; Egito, Eryvaldo S. T.; Gremião, Maria Palmira Daflon [UNESP]; Pohlmann, Adriana Raffin; Guterres, Silvia S. (MDPI, 2018)
Melanoma is the most aggressive and lethal type of skin cancer, with a poor prognosis because of the potential for metastatic spread. The aim was to develop innovative powder formulations for the treatment of metastatic melanoma based on micro- and nanocarriers containing 5-fluorouracil (5FU) for pulmonary administration, aiming at local and systemic action. Therefore, two innovative inhalable powder formulations were produced by spray-drying using chondroitin sulfate as a structuring polymer: (a) 5FU nanoparticles obtained by piezoelectric atomization (5FU-NS) and (b) 5FU microparticles of the mucoadhesive agent Methocel™ F4M for sustained release produced by conventional spray drying (5FU-MS). The physicochemical and aerodynamic were evaluated in vitro for both systems, proving to be attractive for pulmonary delivery. The theoretical aerodynamic diameters obtained were 0.322 ± 0.07 µm (5FU-NS) and 1.138 ± 0.54 µm (5FU-MS). The fraction of respirable particles (FR%) were 76.84 ± 0.07% (5FU-NS) and 55.01 ± 2.91% (5FU-MS). The in vitro mucoadhesive properties exhibited significant adhesion efficiency in the presence of Methocel™ F4M. 5FU-MS and 5FU-NS were tested for their cytotoxic action on melanoma cancer cells (A2058 and A375) and both showed a cytotoxic effect similar to 5FU pure at concentrations of 4.3 and 1.7-fold lower, respectively.
Keywords: 5-fluorouracil; Biopolymers; Cytotoxicity; Metastatic melanoma; Microparticles; Nanoparticles; Pulmonary delivery